Passive flow control on a ground-effect diffuser using an inverted wing - Ehirim, Obinna; Knowles, Kevin; Saddington, Alistair J.; Finnis, Mark V. (Society of Automotive Engineers (SAE), 2018)
In this experimental and computational study a novel application of aerodynamic principles in altering the pressure recovery behavior of an automotive-type ground-effect diffuser was investigated as a means of enhancing downforce. The proposed way of augmenting diffuser downforce production is to induce in its pressure recovery action a second pressure drop and an accompanying pressure rise region close to the diffuser exit. To investigate this concept with a diffuser-equipped bluff body, an inverted wing was situated within the diffuser flow channel, close to the diffuser exit. The wing’s suction surface acts as a passive flow control device by increasing streamwise flow velocity and reducing static pressure near the diffuser exit. Therefore, a second-stage pressure recovery develops along the diffuser’s overall pressure recovery curve as the flow travels from the diffuser’s low pressure, high velocity inlet to its high pressure, low velocity exit. Consequently, downforce production is increased with the use of the wing. Across the range of ride heights investigated, computational fluid dynamics simulations, validated against wind tunnel measurements, show an increase in downforce, with the increase reaching a high of about 12% relative to the baseline (without the wing). However, the increment in downforce occurred at relatively high ride heights but not once the diffuser started stalling at relatively low ride heights.